Factor of education in transition from ascription to achievement - Ozbolat, Abdullah (Elsevier Science Bv, 2012)
This study is basically meant by the transition from ascription to achievement that socioeconomic status started to be determined by achievement through education rather than role of father. Gerdibi villagers were chosen due to its structure that leads to geographic mobility from parents to children and intergenerational social mobility through education. In the sample of Gerdibi villagers, some findings showed that education is an effective factor in transition from ascription to achievement. Results of area study revealed that the differentiation of educational background from parents to children according to education between generation, profession and socioeconomic status also changed the professional status between generations and thus, explanation of background of current socioeconomic status changed. (C) 2012 Published by Elsevier Ltd.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Ascription; Achievernet; Status; Education; intergenerational Social Tlobiliiv; Gerdibi Villagers